2020
DOI: 10.29344/0717621x.41.2280
|View full text |Cite
|
Sign up to set email alerts
|

Alfabetización académica chilena: revisión de investigaciones de una década

Abstract: Esta revisión bibliográfica profundiza en el estado de desarrollo y tendencias de los estudios sobre alfabetización académica en Chile. Se analizan las investigaciones empíricas chilenas publicadas durante una década en revistas indexadas en WoS y Scopus. Los 24 estudios encontrados sugieren una consolidación del campo, caracterizado por investigaciones en ciclos de pregrado, de estudiantes de primero y último año, muestras relativamente pequeñas, diseños cualitativos, y uso de entrevistas y grupos focales com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…Learning a school-or university-level discipline involves acquiring a set of literate and oral discursive practices which can be used to observe and evaluate the learner's acquisition of the discipline and his/her progression in it. The explicit teaching of academic writing through recurrent modeling practices is a powerful tool for learning the contents and skills of a discipline (Calle & Ávila, 2020). In History, intertextual skills are developed through practices that make explicit their rhetorical and epistemological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning a school-or university-level discipline involves acquiring a set of literate and oral discursive practices which can be used to observe and evaluate the learner's acquisition of the discipline and his/her progression in it. The explicit teaching of academic writing through recurrent modeling practices is a powerful tool for learning the contents and skills of a discipline (Calle & Ávila, 2020). In History, intertextual skills are developed through practices that make explicit their rhetorical and epistemological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Snow and Ucelli (2009) define academic language as a "lexical, grammatical, discursive, and disciplinary domain that makes it possible to 'pack' complex and abstract ideas in writing while also enabling subjects to understand school texts and those produced by academic communities" (in Concha et al, 2010, p. 91). Academic language is learned by means of "academic literacy learning", whose field comprises the set of reading and writing practices acquired in order to access and participate in the cultures of each discipline (Calle & Ávila, 2020;Carlino, 2003). The visibilization of these literate practices in school and university education has revealed that their learning and teaching are highly specialized and sophisticated rather than evident, instrumental, or basic (Ávila et al, 2013).…”
Section: Introduction: Writing To Learn Historymentioning
confidence: 99%
“…La escritura se ha entendido, en este sentido, como un mecanismo de interacción que se produce en el proceso formativo, abarcando diferentes ámbitos y trayectorias a través del currículum durante la formación disciplinar (Concha et al, 2017), y cuyas funciones epistémicas (Calle-Arango y Ávila-Reyes, 2019), retóricas (Ávila, 2017) y expresivas (Concha et al, 2017) permiten aprender y transformar los conocimientos disciplinares, adquirir saberes sobre formas específicas de comunicación escrita y favorecer espacios para la expresión de la subjetividad, la perspectiva propia y la experiencia de cada estudiante en su rol de escritor o escritora (Navarro, 2021). En el caso de los y las estudiantes de la Escuela de Carabineros, el desarrollo de esta competencia se orienta a mejorar las interacciones con la ciudadanía y, para ello, el desarrollo de habilidades comunicativas es fundamental en un contexto biopsicosocial (Calle-Arango y Ávila-Reyes, 2019).…”
Section: Antecedentes Teóricosunclassified
“…Research on university students as writers in the disciplines is still a vast area of exploration. Despite the advances at an international and national level ( Calle-Arango and Avila-Reyes, 2020 ), new descriptions and reflections must be incorporated that connect the discursive production with the broader educational and professional practices. Thus, the production of laboratory reports stands out within the academic genres used in undergraduate education.…”
Section: Introductionmentioning
confidence: 99%